"Little More than Rich Soil?": The Anatomy and Politics of the Cape Bat Guano Trade, 1890–1920. (1st July 2021) - Snyders, Hendrik
Abstract: The bat guano trade, although a small, localised, and secondary enterprise was as significant for the nineteenth and early twentieth century Cape fertiliser trade as its more lucrative and prominent counterpart, the seabird guano trade. Located in relatively inaccessible and geographically dispersed caves on the Southern Cape coast and following a long struggle to be acknowledged as a useful fertiliser, the product became part of and contributed to the generation of continuous conflict between the colonial authorities, local farmers, and entrepreneurs about cheap guano. Aided by farmer-politicians, bona fide farmers and horticulturists continuously agitated for access to a cheap fertiliser while local businessmen with an interest in deriving some income from its exploitation fought for the right to free and unrestricted access to the resource. Resolution of this matter became far more difficult with the dawn of the Union of South Africa where the need to integrate new discoveries in Transvaal resulted in the need for a national policy and a central administration as well as common quality standards. Although relatively low-key and less dramatic, the battle for access to bat guano mirrored that of the seabird guano trade. This article attempts to properly contextualise this branch of the international guano trade and to describe the dynamic interaction between the conflicting parties around matters such as access, policy, and profit. In this regard, it explores and tries to make sense of both the mechanisms used and compromises concluded to ensure the workability of the system during the first two decades of the twenty-first century.